EFFORTS TO FULFILL AND PROTECT PATIENTS’ LEGAL RIGHTS IN HEALTH CARE SERVICES AT MEURAXA REGIONAL GENERAL HOSPITAL, BANDA ACEH CITY. - Rayga Rayyan; T. Riza Zarzani; Marice Simarmata (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The fulfillment and legal protection of patients’ rights are essential components of safe and equitable healthcare services. This study aims to analyze the fulfillment of patients’ rights and the forms of legal protection in healthcare services at a regional public hospital in Indonesia. An empirical juridical method with a qualitative approach was employed, combining statutory analysis with field data collected through in-depth interviews, observation, and documentation. The findings indicate that patients’ rights have generally been fulfilled, particularly the rights to information, informed consent, privacy, and healthcare services in accordance with applicable standards. Preventive legal protection is implemented through the application of standard operating procedures, while repressive legal protection is carried out through complaint mechanisms and professional disciplinary enforcement. However, the effectiveness of legal protection is influenced by institutional commitment, the understanding of health workers regarding patients’ rights, and the accessibility of complaint mechanisms for patients. These findings provide an empirical overview of the implementation of legal protection for patients’ rights in public hospital healthcare services and may serve as a reference for improving governance and accountability in public healthcare institutions.